SCREEN ATTRACTIONS: BETWEEN VISUAL AND NARRATIVE / АТТРАКЦИОНЫ ЭКРАНА: МЕЖДУ ВИЗУАЛЬНЫМ И НАРРАТИВНЫМ - KOZLOV EVGENY V. / КОЗЛОВ Е.В. (Наука телевидения)
Based on a number of provisions of aesthetics and film semiotics, the article interprets the structural features of the attractions of screen civilization and analyzes their varieties in the context of serial art products that reveal their structural and receptive specifics. The attraction has its deep reflection in the mental structure. The attraction appears as an external manifestation of the phantasm. The attraction, like phantasm, resonates on the basis of the difference of several episodes with which it is connected by the relation of causality. Art “produces the phantasm theatrically” (according to G. Deleuze), bringing the quasi-event from the depths of the psychic to the surface, into the symbolic space of artistic fiction. Phantasm is an internal resonance of the two series, while an attraction appears as an external manifestation and effect of the difference between the causal series (visual/narrative; rational/emotional; singular/universal, fictional/real, presence/absence). Based on the disjunctive synthesis of these series, an attraction occurs in films and comic books on foot of the ultimate (limiting the space for fiction) and the transcendent, going beyond the screen limitations, canceling the conventional barriers for fiction. A locomotive rushing into the auditorium from the cinema screen is an example of an attraction that is considered in the screen civilization as an attractive and sensational element of an artistic program. Such a cinema attraction is addressed almost exclusively to the eye, and for its success the resonance is important, which is provided by the predominance of the visual over the narrative. The juxtaposition, going back to André Gaudreault’s semiotics, between a cinematic attraction (in which the visual component is almost unchallenged) and that of films (filmique), in which the narrative might have a chance for revenge, reveals an interesting response in the culture of the modern series. A film attraction appears as a result of the constructive interaction of visual perceptions and creative interpretations of the plot, shaped by the recipients themselves. It is assumed that a cliffhanger, which is often used in the series, can be such an attraction. In the modern storytelling, the art of creating and maintaining intrigue is endowed with fundamental importance. The attraction of the series is aimed at the continuation, at the teaser of the next episode, which should look as attractive as possible and seem to be an artistic product absolutely mandatory for consumption. The techniques and practices developed for these purposes become systematically updated in the media space, which nowadays is literally “infected with cliffhangers”. Основываясь на ряде положений эстетики и киносемиотики, статья предлагает интерпретацию структурных особенностей аттракционов экранной цивилизации и анализ их разновидностей в контексте сериальной художественной продукции, обнаруживающей свою структурную и рецептивную специфику. Аттракцион имеет свое глубинное отражение в психической структуре и предстает в виде внешнего проявления фантазма. Аттракцион, как и фантазм, резонирует на основе различия нескольких серий, с которыми он связан отношением каузальности. Искусство осуществляет «театрально-сценическое производство фантазма» (по Ж. Делезу), выводя квазисобытие из глубин психического на поверхность, в знаковое пространство художественного вымысла. Фантазм — внутренний резонанс двух серий, аттракцион же предстает в качестве внешнего проявления и эффекта различия каузальных серий (визуальное/нарративное; рациональное/эмоциональное; сингулярное/универсальное, вымышленное/реальное, присутствие/отсутствие). На основе дизъюнктивного синтеза указанных серий аттракцион в кино и комиксах возникает из предельного (ограничивающего пространство для фикции) и запредельного, выходящего за экранные ограничения, отменяющего условные преграды для художественного вымысла. Локомотив, устремляющийся в зрительный зал с киноэкрана, является примером аттракциона, который в экранной цивилизации рассматривается в качестве притягательного и сенсационного элемента художественной программы. Такой киноаттракцион обращен почти исключительно к глазу и для его успешности важен резонанс, который обеспечен преобладанием визуального над нарративом. Восходящее к киносемиотике Андре Годро противопоставление кинематографического аттракциона (в котором практически безраздельно царит визуальное) фильмовому (filmique), в котором нарратив мог бы иметь шансы на реванш, обнаруживает небезынтересный ответ в культуре современных сериалов. Фильмовый аттракцион предстает в качестве результата конструктивного взаимодействия визуальных восприятий и творческих интерпретаций сюжета, которые выстраивает сам реципиент. Представляется, что таким аттракционом может быть используемый в сериалах клиффхэнгер. Искусство создания и поддержания интриги наделяется в современном пространстве повествования принципиальной важностью. Аттракцион сериала нацелен на продолжение, на анонсируемый последующий фрагмент произведения, который должен казаться реципиенту максимально привлекательным и художественной продукцией совершенно обязательной для потребления. Разработанные для указанных целей приемы и техники становятся систематически актуализируемыми в медийном пространстве, буквально «зараженном клиффхэнгером».